Hospital Supply Chain Management by Implementing RFID - Erick C. Jones; Shalini Gupta; Soma sekar Balasubramanian (International Journal of Supply Chain Management, 2015)
Abstract- Radio Frequency Identification (RFID) systems have been successfully applied and shown its worth in many fields of manufacturing, transportation, agriculture, healthcare and supply chain just to name a few. The use of RFID in healthcare and hospital services has increased significantly over the years due to its credibility and accuracy. RFID technology is acting crucial in item level tracing and tracking systems in hospital scenarios. The aim of the paper is to express and display the role of RFID technology in maintaining the inventory level of medicines and surgical items in hospital warehouses and increase its impact in healthcare. One of the crucial points that should be noted in healthcare is that the medicines and surgical items should be made available at any point of time. The implementation of RFID technology in this area is to ensure patient safety and satisfaction by maintaining a perfect inventory of medicines and surgical items. Keywords- Enterprise management, SCOR model, RFID, healthcare, hospital.